Linguistic Expression of Female Identity in Modern British Fiction - Gaboyan, Aspram («Տիր» հրատ.)
The study of the relationship between gender and language is carried out by applying general linguistic, psycholinguistic, and pragmatic principles. The interdisciplinary examination of gender and language is perhaps due to the fact that gender discourse touches upon such urgent issues as women's equality and their position in society. This part of the research refers to all the theoretical propositions, thanks to which the relationship between gender and language is covered, defining the features by which the communication tactics of women and men are determined. A thorough research and analysis of factual material were carried out. In other words, examining the word units, grammatical patterns, and syntax used by British authors to describe a woman's identity, an attempt was made to present the general characteristics of the image of a woman and her communication tactics. The obtained results can be used in theoretical and practical courses studying gender discourse. Գենդերի և լեզվի փոխկապակցվածության ուսումնասիրությունն իրականացվում է հանրալեզվաբանական, հոգելեզվաբանական, գործաբանական դրույթների կիրառմամբ։ Գենդերի և լեզվի միջգիտակարգային քննությունը, թերևս, պայմանավորված է այն փաստով, որ գենդերային դիսկուրսն անդրառնում է այնպիսի հրատապ խնդիրների, ինչպիսիք են՝ կանանց իրավահավասարությունը և նրանց զբաղեցրած դիրքը հասարակության մեջ։ Աշխատանքի որոշ հատված անդրադարձ է կատարում բոլոր այն տեսական դրույթներին, որոնց շնորհիվ գենդեր և լեզու փոխհարաբերությունները լուսաբանվում են՝ սահմանելով այն առանձնահատկությունները, որոնց միջոցով կանանց և տղամարդկանց հաղորդակցական մարտավարությունները որոշարկվում են։ Изучение взаимосвязи пола и языка осуществляется с использованием общелингвистических, психолингвистических и прагматических принципов. Междисциплинарное рассмотрение гендера и языка, возможно, связано с тем, что гендерный дискурс затрагивает такие актуальные вопросы, как равноправие женщин и их положение в обществе. Часть работы рассматриваются все те теоретические положения, благодаря которым освещаются взаимоотношения пола и языка, определяются особенности, которыми определяется тактика общения женщин и мужчин.
Keywords: Literature